Black for a Day : White Fantasies of Race and Empathy - Gaines, Alisha (Book collections on Project MUSE., 2017)
"In 1948, journalist Ray Sprigle traded his whiteness to live as a black man for four weeks. A little over a decade later, John Howard Griffin famously 'became' black as well, traveling the American South in search of a certain kind of racial understanding. Contemporary history is littered with the surprisingly complex stories of white people passing as black, and here Alisha Gaines constructs a unique genealogy of 'empathetic racial impersonation' - white liberals walking in the fantasy of black skin under the alibi of cross-racial empathy. At the end of their experiments in 'blackness, ' Gaines argues that these debatably well-meaning white impersonators arrived at little more than false consciousness"--